The Effect of DHF Education on DHF Prevention Knowledge of 5th and 6th Grade Students of SDN Purwotengah II Mojokerto - Fernanda Irfatul Laily; Lynda Rossyanti; Sulistiawati Sulistiawati (Faculty of Medicine Universitas Airlangga, 2020)
Introduction: Cases of Dengue Haemorrhagic Fever (DHF) are still one of the public health diseases that are widespread in the world including tropical and subtropical regions in Indonesia. One of the factors that influence DHF is prevention of DHF education for elementary school students considering the incidence of DHF is fluctuating and has the potential to attack children.Methods: A pre-experimental, with one group pre and post-test design. The sample of this research were 5th and 6th grade students of SDN Purwotengah II Mojokerto. There were 55 respondents with total sampling technique. Data collection was done by giving questionnaires at pretest, post-test 1, and post-test 2 after two days of education. Data analysis used Friedman test, followed by Wilcoxon test to find out different locations.Results: Based on Friedman test on pretest, post-test 1, and posttest 2 after two days of education, p value = 0.000 (p < 0.05). Followed by Wilcoxon test at pretest with post-test 1, p value = 0.000 (p < 0.05) and on post-test 1 with post-test 2 after two days of education, p value = 0.164 (p > 0.05)Conclusion: There was an effect of education on the knowledge of pretest, post-test 1 and post-test 2 after two days of education for students. The effect of education on the knowledge of pretest and post-test 1 contained differences in significance, while the effect of education on post-test 1 and post-test 2 after two days of education contained no difference in significance.